Scarring Effects and Asymmetric Respons of Food Security to Climate Shocks: A PMG-ARDL Econometric Analysis for North African Countries(1990-2024) - Benmensour , Lilia; Zedira , Charefeddine; Hebbaz , Nahed (Journal of Ecohumanism, 2026)
This study investigates the equilibrium and dynamic relationship between climate change and food security in North Africa from 1990 to 2024, with a specific focus on analyzing "Scarring Effects" and the asymmetric response of food systems to environmental shocks. Utilizing the Pooled Mean Group (PMG-ARDL) heterogeneous dynamic panel model and the Wald test for linear constraints, the findings reveal a long-term co-integrating relationship, confirming that food stability is inherently tethered to climate stability. The results indicate that persistent temperature rises function as a "structural brake," diminishing agricultural efficiency. Furthermore, the study identifies a sharp asymmetry; the destructive impact of drought years significantly outweighs the recovery phase during periods of rainfall abundance. This phenomenon leaves deep "scars" on farmers’ productive assets, leading to a profound inertia in returning to equilibrium, requiring approximately 2.7 years to dissipate the shock. The study concludes that ongoing demographic growth, coupled with climate fragility, necessitates a shift in the region’s "developmental doctrine" toward proactive food sovereignty and the implementation of smart insurance systems that safeguard the production base, rather than relying solely on transient consumption subsidies.